Securing the Commons in India: Mapping Polycentric Governance. Issue 1 (18th June 2021) - Meinzen-Dick, Ruth; Chaturvedi, Rahul; Kandikuppa, Sandeep; Rao, Kaushalendra; Rao, Jagdeesh Puppala; Bruns, Bryan; ElDidi, Hagar
Common pool land and water resources in India play vital, but often overlooked, roles in livelihoods and ecosystem services. These resources are subject to the authority of various government departments and are often managed in ways that result in uncertain tenure for the people who depend on these resources for fodder, fuel, water, and other products. An Indian NGO, the Foundation for Ecological Security, has developed a process for "commoning"—assisting communities to secure the commons by forming inclusive local institutions to manage the resources, and to work with the different government departments to gain stronger rights to the commons. This study examines how the polycentric governance of natural resource commons shapes the ability of communities to do effective commoning, with particular reference to appropriation and provisioning rules. Using participatory network-mapping in FES sites in Andhra Pradesh and Karnataka states, we identify the constellation of actors involved in the commons, the relationships among them, and community knowledge of these arrangements. The results reveal the complex flows of resources, information, and authority related to commons, with programs and agencies across different sectors, offering different opportunities and requirements, for commons management. The Net-maps show linkages that are present, and others that are missing or not well-understood, Net-mapping helps assess the extent of community understanding of the polycentric governance of the commons, and can help identify opportunities to strengthen participatory processes for planning and implementation.